2014
DOI: 10.1042/cs20140101
|View full text |Cite
|
Sign up to set email alerts
|

The Bioenergetic Health Index: a new concept in mitochondrial translational research

Abstract: Bioenergetics has become central to our understanding of pathological mechanisms, the development of new therapeutic strategies and as a biomarker for disease progression in neurodegeneration, diabetes, cancer and cardiovascular disease. A key concept is that the mitochondrion can act as the ‘canary in the coal mine’ by serving as an early warning of bioenergetic crisis in patient populations. We propose that new clinical tests to monitor changes in bioenergetics in patient populations are needed to take advan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
357
1
14

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 302 publications
(383 citation statements)
references
References 47 publications
11
357
1
14
Order By: Relevance
“…Recently, we have proposed that inflammatory cells, such as monocytes/macrophages, neutrophils or lymphocytes, can act as a biomarker of inflammation-associated mitochondrial dysfunction defined as changes in cellular bioenergetics [11][12][13]. Taken together, these findings suggested to us the hypothesis that the monocytes isolated from the PO-PCF, which is more pro-oxidant than the plasma, would exhibit increased mitochondrial dysfunction compared with cells isolated from the patients' blood.…”
Section: Introductionmentioning
confidence: 50%
See 4 more Smart Citations
“…Recently, we have proposed that inflammatory cells, such as monocytes/macrophages, neutrophils or lymphocytes, can act as a biomarker of inflammation-associated mitochondrial dysfunction defined as changes in cellular bioenergetics [11][12][13]. Taken together, these findings suggested to us the hypothesis that the monocytes isolated from the PO-PCF, which is more pro-oxidant than the plasma, would exhibit increased mitochondrial dysfunction compared with cells isolated from the patients' blood.…”
Section: Introductionmentioning
confidence: 50%
“…We have recently demonstrated that the individual parameters from the mitochondrial stress test are interactive and that they can be integrated into a single value representing the profiles shown in Figures 1(A) and 1(B) known as the BHI [11]. As shown in Figure 2(A), BHI is significantly different (P = 0.030) between the healthy controls and the monocytes isolated from the blood from patients following surgery.…”
Section: Measurement Of the Bioenergetic Health Indexmentioning
confidence: 84%
See 3 more Smart Citations